Pathological Role of Natural Killer Cells in Parkinson's Disease: A Systematic Review - Zhang, Le; Zhang, Yingshuang; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2022)
Parkinson disease (PD) is one of the common neurodegenerative diseases characterized by selective degeneration of dopaminergic neurons in the substantia nigra, and misfolding α-synuclein aggregation is thought to contribute to the pathology of it. Studies have shown that immune‐inflammatory responses involve in PD development and play an important role in α-synuclein scavenge. Natural killer (NK) cells are first responders in immune cells and can directly promote immune defense by cytotoxicity and secreting cytokines. Recent discoveries suggest that NK cells are increasingly recognized in PD pathologic features. However, the mechanisms underlying it have not been fully understood. In this review, we systematically retrieved and evaluated published evidence about the functions of NK cells in PD. We find alterations of NK cell numbers and cytotoxicity in the process of PD, and it seems that NK cells play a neuroprotective role in PD pathogenesis, which may reveal novel targets in PD therapy.